Evaluating the reality of E-learning in Syrian universities during crises "Corona crisis as a model" (Journal of Hama University, 2022)
The aim of the research is to study the reality of E-learning in Syrian universities during the Corona crisis, by evaluating the effectiveness of E-learning, and the availability of its requirements in Syrian universities, the researcher adopted the descriptive analytical approach, Where the statistical analysis program Spss 25 was used to analyze the data collected by relying on the questionnaire tool, As for the research sample, it was 424 students in Syrian universities, The most important findings of the study are the results of the ineffectiveness of E-learning, and the lack of its requirements in Syrian universities during the Corona crisis, The researcher attributed this to the lack of controls regulating the educational process to achieve its goals, and the lack of carefully studied strategies for applying e-learning in Syrian universities, Based on the previous results, the researcher recommended the necessity of creating a directorate in the Ministry of Higher Education and Scientific Research to be concerned with strategic planning for the application of E-learning in Syrian universities, and the quality assurance centers in the faculties to continuously evaluate the effectiveness of E-learning, and the availability of its requirements in each faculty, and to submit recommendations to the university presidency, to work on developing a strategic plan to establish an appropriate infrastructure for the transition to E-learning.
Keywords: E-learning, Crises, Syrian universities, Corona crisis.